Exploring Research Trends in the Indonesian Archipelago’s New National Capital - Hamjen, Hilarion; Said, Laila Refiana (AIBPM Publisher, 2023)
The Indonesian Government announced the relocation of the National Capital from Jakarta to East Kalimantan Province in 2019. The term ‘Capital of the Archipelago ' or Ibu Kota Nusantara (IKN) was approved as the name of the new capital of the Republic of Indonesia. This study conducted visualization and bibliometric analysis using VOSviewer 1.6.20 from 100 scientific articles with the keyword